Patterns of media and social media use in generation z in Indonesia - Evita, Nona; Prestianta , Albertus Magnus; Asmarantika , Rossalyn Ayu (Jurnal Studi Komunikasi, 2023)
Industry 4.0 makes everything shift from conventional to digital, and this conversion also changes media consumption habits among Generation Z. This generation is important because Generation Z is the largest digital consumer in Indonesia. This study discusses Generation Z’s media consumption in Indonesia during the pandemic. This study aims to discover how the pattern of media consumption and use of social media in Generation Z in the pandemic era coincides with the industrial era 4.0. This study uses a survey method of 1177 respondents, and this type of research is descriptive exploratory with purposive sampling. The age range of respondents is 15-25 years from all over Indonesia. An interesting finding from this study is that the media that are the main gates of Generation Z in getting information are instant messaging applications and social media. The primary purpose of media from Generation Z is to seek entertainment, but Generation Z is also looking for non-entertainment/serious information, such as information related to education and work.